Analysis of Factors Causing Pending BPJS Inpatient Claims at dr. H. Koesnadi General Hospital, Bondowoso - Istianingsih, Noviana; Mudiono, Demiawan Rachmatta Putro; Rachmawati, Ervina; Suyoso, Gandu Eko Julianto (P3M Politeknik Negeri Jember, 2025)
Dr. H. Koesnadi Bondowoso General Hospital recorded 25 out of 4,918 inpatient BPJS claim files (1.5%) in pending status from February to April 2024. This delay impacted the timely disbursement of BPJS claim funds and disrupted the hospital’s cash flow. The aim of this study was to analyze the factors contributing to pending BPJS inpatient claims. This research employed a qualitative approach, with data collected through in-depth interviews, observations, and documentation. The research subjects consisted of one Head of Control Installation, two DPJPs (attending physicians), one Internal Verifier, two Coders, two Entry Officers, and one Administrative Officer. The study found that motivational factors did not contribute to pending claims, as responsibilities had already been assigned to the DPJPs, coders, and entry officers. However, opportunity-related factors caused pending claims due to uneven training and the absence of job descriptions specifying the tasks of claim officers. Ability-related factors also contributed to pending claims, including insufficient staff knowledge, differences in perception between DPJPs and BPJS regarding the claims process, and the presence of new, inexperienced staff. The main problem identified was a lack of staff knowledge about the BPJS claim submission process. Proposed solutions include providing regular socialization and education on claim procedures as well as sending staff to relevant training programs.